2016
DOI: 10.1177/1474904116641422
|View full text |Cite
|
Sign up to set email alerts
|

How to construct an organizational field: Empirical educational research in Germany, 1995–2015

Abstract: Over the past two decades, educational research in Germany has undergone unprecedented changes. Following large-scale assessments such as the Trends in International Mathematics and Science Study (TIMSS) and the Programme for International Student Assessment (PISA), and a political interest in evidence-based policy-making, quality assessment and internationalization, direct involvement of national decision-makers has led to the establishment of new organizations, programs, funding structures, professorships, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 56 publications
2
38
0
Order By: Relevance
“…This confirms continuity with regard to research governance observed in particular for Norway in the 1990s (Larsen, 2000). (Zapp & Powell, 2016.…”
Section: The Regulative Dimensionsupporting
confidence: 80%
“…This confirms continuity with regard to research governance observed in particular for Norway in the 1990s (Larsen, 2000). (Zapp & Powell, 2016.…”
Section: The Regulative Dimensionsupporting
confidence: 80%
“…Our case illustrates how international stimuli, in the guise of large-scale assessments, evidence-based policy-making experiments, and a globe-spanning quantitative research paradigm in general trigger cognitive and organizational changes in a national setting (Zapp and Powell 2016). Such largescale shifts are supported by a highly utilitarian science for development policy model institutionalized on highly collective levels and beyond concrete evidence of its viability (Drori et al 2003).…”
Section: Discussionmentioning
confidence: 91%
“…Nor did Germany's ER community show much interest in joining international debates on achievement testing and performance assessment; now routine practice. Germany hardly participated in large-scale assessments until the mid-1990s, thus reducing opportunities for quantitative researchers to contribute analyses (Aljets 2015;Zapp and Powell 2016).…”
Section: Educational Scholarship In Germany In Modementioning
confidence: 99%
See 2 more Smart Citations